1994
DOI: 10.1021/la00019a016
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Aqueous Dispersions of Colloidal Boehmite Rods

Abstract: We report the phase behavior of aqueous dispersions containing rodlike boehmite particles with two different average lengths, 130 and 280 nm, with length-to-width ratios of approximately 8 and 20, over a range of ionic strengths. At low salt concentrations, where the particle interaction is predominantly repulsive, a separation into an isotropic upper phase and a birefringent lower phase occurs in the system containing the high-aspect-ratio particles. This phase separation was not observed in the case of dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 1 publication
13
148
1
Order By: Relevance
“…Thus, the present setup of a pinning-field line can be experimentally realized by considering an elongated cylindrical colloid immersed in a critical binary mixture, in the limit of small radius and large length of the colloid. A variety of rodlike particles are experimentally available, such as Boehmite rods [77,78], gold nanorods [79], carbon nanotubes [80], microtubules [81], lipid tubules [82], the mosaic tobacco virus [83], and cylindrical micelles [84].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Thus, the present setup of a pinning-field line can be experimentally realized by considering an elongated cylindrical colloid immersed in a critical binary mixture, in the limit of small radius and large length of the colloid. A variety of rodlike particles are experimentally available, such as Boehmite rods [77,78], gold nanorods [79], carbon nanotubes [80], microtubules [81], lipid tubules [82], the mosaic tobacco virus [83], and cylindrical micelles [84].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…4,17,22 The strong dependence of the phase behavior on the size of the polymer has been stressed; 1,19,[21][22][23] below a certain minimum polymer size there is no demixing in the fluid phase. Varying the size of the polymer allows the effective colloid-colloid interaction to be varied in a way which is impossible for simple substances such as argon.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Earlier work by one of us and Jackson 1 has shown that a mixture of rods of finite diameter with rods of zero diameter shows extensive immiscibility in the isotropic fluid phase. The mixture is an idealized model of a mixture of synthetic colloidal rods 4 and a rigid rodlike polymer. 5 Here we generalize the theory of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Their aqueous dispersions exhibit flow birefringence, thixotropy and elasticity [5]. Like many of the colloidal rod-like systems, they are capable of forming a nematic phase above a certain particle concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to boehmite, well-known inorganic examples that form a nematic phase are imogolite, V 2 O 5 and b-FeOOH [6]; whereas cellulose microcrystals, poly(tetrafluoroethylene) whiskers and tobacco mosaic virus are some other examples of organic systems. [5] In aqueous boehmite dispersions, the particles are stabilized by electrical double-layer repulsion [7]. Addition of an organic solvent destroys the repulsive interaction and results in flocculation of the particles.…”
Section: Introductionmentioning
confidence: 99%